Visual Metaphors of Depression in BoJack Horseman - Ortiz, Maria J. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
BoJack Horseman is an animated television series that revolves around the life of an anthropomorphic horse. A major reason for the series’ reputation and positive reviews is its accurate portrayal of depression, mental illness, and trauma. Animation is best suited to illustrate aesthetically inventive metaphors of emotions, as it can display conceptual metaphors that are unavailable to language. The study objective is to analyse the visual manifestations of conceptual metaphors of depression in BoJack Horseman. Additionally, it is argued how some of them can be considered humorous, so viewers understand the characters’ feelings but are distanced at the same time from the suffering.